2019
DOI: 10.3390/nu11010180
|View full text |Cite
|
Sign up to set email alerts
|

Validity of an Abbreviated, Clinically Feasible Test for Postprandial Lipemia in Healthy Adults: A Randomized Cross-Over Study

Abstract: Background: A large post-meal triglyceride (TG) response is an independent risk factor for cardiovascular disease, but postprandial lipemia assessments are not clinically practical in their current form. Therefore, we assessed the validity of an abbreviated, clinically feasible protocol in measuring postprandial lipemia. Method: Eighteen healthy adults (8 male and 10 female) completed 3 high-fat meal trials in random order: (1) a Standard in Lab (SL) protocol wherein blood draws (to determine TG) were made fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Our group has devoted work to this issue with some success. We recently determined that an abbreviated and simplified fat tolerance test was both valid and reliable ( 168 , 169 ) . With this protocol, blood draws only occur at baseline and 4 h, and participants are allowed to leave the laboratory and engage in normal daily activities as long as they do not eat or perform planned exercise.…”
Section: Clinical Implementationmentioning
confidence: 99%
“…Our group has devoted work to this issue with some success. We recently determined that an abbreviated and simplified fat tolerance test was both valid and reliable ( 168 , 169 ) . With this protocol, blood draws only occur at baseline and 4 h, and participants are allowed to leave the laboratory and engage in normal daily activities as long as they do not eat or perform planned exercise.…”
Section: Clinical Implementationmentioning
confidence: 99%
“…The effect of a high-protein (HP) meal in a shorter timeframe of 3-h has been evaluated only by Shah et al (2017, 2018) in lean and obese/overweight subjects. In clinical practice, there is a demand for reliable and practical assessment tools to investigate postprandial lipoproteinemia as a risk marker for CVD (Sciarrillo et al, 2019). In this study, we aimed to determine if a meal rich in carbohydrates, fat, or protein differentially alters the postprandial lipoprotein particle concentration as early as 2-h after meal challenge using a commercially available nuclear magnetic resonance (NMR) method.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 113 studies showed that the level of TG 4 h after the fat tolerance test was the most representative ( 143 ). Research showed that compared with the detection of postprandial TG, increment and total area under the curve before and after the meal tested hourly for 6 h and subjects that had blood drawn before and 4 h after meals without restriction of activity had results similar to those of the previous test, which provided a simple method for the detection and application of postprandial lipemia ( 144 ). Maraki et al ( 145 ) have also shown that postprandial lipemia may be accurately described by the OFTT with reduced frequency of blood sampling.…”
Section: Conclusion and Perspectivementioning
confidence: 99%